Effect of recombinant human epidermal growth factor on cutaneous scar quality in thyroidectomy patients. (April 2015) - Shin, Jung U; Kang, Sang-Wook; Jeong, Jong Ju; Nam, Kee-Hyun; Chung, Woong Youn; Lee, Ju Hee
Abstract Background: Epidermal growth factor (EGF) decreases inflammatory cell infiltration and TGF-β expression during wound healing. Several clinical studies show that recovery of various ulcer wounds, such as diabetic and radiation ulcer, is promoted by EGF. Objective: To evaluate effects of recombinant human epidermal growth factor (rhEGF) on cutaneous scar quality after thyroidectomy. Method: Scar quality was evaluated by Vancouver scar scale (VSS) in two groups of female thyroidectomy patients (control, n = 11; rhEGF-treated, n = 10). Scar erythema, pigmentation, elasticity and hydration were measured by mexameter, cutometer and corneometer. Results: Scar pliability (at 4 weeks) and thickness (2 weeks) after surgery were significantly lower in the rhEGF group than control. Total VSS score was significantly lower in the rhEGF group after 4 weeks. However, erythema, pigmentation, elasticity and hydration of the scar were not significantly different between groups. Conclusion: The early use of rhEGF in surgical wound healing may improve cutaneous scar quality.